AZERBAIJAN: THE NEW PRESIDENT TAKES HIS FIRST STEPS - CHEPURIN, Alexander (CENTRAL ASIA AND THE CAUCASUS, 2004)
In the mid-1980s, as newcomer to the U.S.S.R. Foreign Ministry, I took part in the talks between Heydar Aliev, member of the Politburo of the C.P.S.U. Central Committee, First Deputy.Chairman of the Council of Ministers of the U.S.S.R., and the Italian premier at that time. I was immediately struck by Aliev’s obvious charisma, which I was further witness to during bi-lateral talks and contacts within the Caucasian Four. It was the time of his “political Renaissance” as president of independent Azerbaijan. I should say that nearly all of the almost 80 percent of the votes his son won at the presidential elections on 15 October, 2003 (a truly Caucasian result) were cast for Heydar Aliev himself, the man who dominated the political scene in Azerbaijan for nearly three and a half decades since 1969. The only time of troubles, which was marked by eco-nomic degradation, bloodshed in Nagorny Karabakh, and political chaos, was a very short period between the late 1980s and early 1990s when other people ruled the republic. In fact, there is every reason to call Heydar Aliev the architect of mod-ern Azerbaijan. The newly elected president described his political course as a policy of continuity.